FAM20A Gene Mutation: Amelogenesis or Ectopic Mineralization? - Lignon, Guilhem; Beres, Fleur; Quentric, Mickael; Rouzière, Stephan; Weil, Raphael; De La Dure-Molla, Muriel; Naveau, Adrien; Kozyraki, Renata; Dessombz, Arnaud; Berdal, Ariane (Frontiers in Physiology, 2017)
Background and objective: FAM20A gene mutations result in enamel renal syndrome (ERS) associated with amelogenesis imperfecta (AI), nephrocalcinosis, gingival fibromatosis and impaired tooth eruption. FAM20A would control the phosphorylation of enamel peptides and thus enamel mineralization. Here, we characterized the structure and chemical composition of unerupted tooth enamel from ERS patients and healthy subjects. Methods: Tooth sections were analyzed by Scanning Electron Microscopy (SEM), Energy Dispersive Spectroscopy (EDS), X-Ray Diffraction (XRD) and X-Ray Fluorescence (XRF). Results: SEM revealed that prisms were restricted to the inner-most enamel zones. The bulk of the mineralized matter covering the crown was formed by layers with varying electron-densities organized into lamellae and micronodules. Tissue porosity progressively increased at the periphery, ending with loose and unfused nanonodules also observed in the adjoining soft tissues. Thus, the enamel layer covering the dentin in all ERS patients (except a limited layer of enamel at the dentino-enamel junction) displayed an ultrastructural globular pattern similar to one observed in ectopic mineralization of soft tissue, notably in the gingiva of Fam20a knockout mice. XRD analysis confirmed the existence of alterations in crystallinity and composition (versus sound enamel). XRF identified lower levels of calcium and phosphorus in ERS enamel. Finally, EDS confirmed the reduced amount of calcium in ERS enamel, which appeared similar to dentin. Conclusion: This study suggests that, after an initial normal start to amelogenesis, the bulk of the tissue covering coronal dentin would be formed by different mechanisms based on nano to micronodule aggregation. This evocated ectopic mineralization process is known to intervene in several soft tissues in FAM20A gene mutant.